Improved ammonia vapor sensing properties of Al-doped ZnO nanoparticles prepared by sol-gel process. (12th May 2021) - Poul Raj, I Loyola; Gobalakrishnan, S; Praseetha, P K; Chidhambaram, N; Saravanakumar, S; Ganesh, V; AlFaify, S; Algarni, H; Yahia, I S
Abstract: Aluminium-doped ZnO nanoparticles were synthesized using the simple and cost-effective sol-gel route. Their structural, morphological, optical, and ammonia vapor sensing properties were compared with the pristine ZnO sample. The x-ray diffraction results showed that the pristine and Al-doped ZnO samples exhibit a hexagonal structure with the P63mc space group. A detailed structural investigation was carried through the Rietveld refinement technique. The decrease in crystallite size and the increasing nature of the sample's microstrain were observed through the Williamson-Hall (W-H) analysis. 1-D, 2-D, and 3-D electron density distribution in a single unit cell of ZnO nanoparticles were studied with the maximum entropy method and it is confirmed that the ionic nature of the Zn-O bond increases by Al doping. The surface morphology of the samples was altered significantly after the addition of aluminum with ZnO. Aluminium doping causes a notable bandgap broadening in the ZnO nanostructures. A momentous enhancement of ammonia detection sensitivity of 129% at 25 ppm was observed for the ZnO:Al(3%) sample and its response time is greater than the other tested samples. Further, ZnO:Al(3%) sample exhibits the best response and recovery time of 28 and 8 s, respectively. It has also shown a stable ammonia vapor sensing ability for five consecutive cycles.